Improving process reliability by means of detection of weld seam irregularities in copper via thermographic process monitoring - Schaumberger, Kerstin; Beck, M.; Saffer, Judith; Kaufmann, Florian; Ermer, J.; Roth, S.; Schmidt, Michael (Procedia Manufacturing, 2019)
Laser beam welding plays an important role in automotive industry as it offers a number of advantages. These include contactless joining, localized energy input, thermally and mechanically durable welds and low electrical contact resistance of the bonded connections. The latter is exploited in the laser beam welding of copper contacts as used for electrical connections in e-mobility. However, copper entails a higher susceptibility to seam defects due to the metallurgical properties compared to, for example, car body materials which in many cases are processed by laser beam as well. In order to meet the high standards of the automotive industry an inline validation of the connections is essential. A suitable method is the monitoring of the welding process by means of thermography which has already proven itself for other metals and joining techniques but has not yet been investigated in detail for laser beam welding of copper. Consequently, this paper deals with the possibilities of thermographic process monitoring in laser beam welding of copper components. It examines the extent to which defects can be registered; so far pores have been detected reliably up to a minimal diameter of 0.5 mm.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Copper; Defects; Infrared thermography; Inline monitoring; Laser beam welding